Integrative analysis of global gene expression identifies opposite patterns of reactive astrogliosis in aged human prefrontal cortex (2018)
The prefrontal cortex (PFC) is one of the brain regions with more prominent changes in human aging. The molecular processes related to the cognitive decline and mood changes during aging are not completely understood. To improve our knowledge, we integrated transcriptomic data of four studies of human PFC from elderly people (58–80 years old) compared with younger people (20–40 years old) using a meta-analytic approximation combined with molecular signature analysis. We identified 1817 differentially expressed genes, 561 up-regulated and 1256 down-regulated. Pathway analysis revealed down-regulation of synaptic genes with conservation of gene expression of other neuronal regions. Additionally, we identified up-regulation of markers of astrogliosis with transcriptomic signature compatible with A1 neurotoxic astrocytes and A2 neuroprotective astrocytes. Response to interferon is related to A1 astrocytes and the A2 phenotype is mediated in aging by activation of sonic hedgehog (SHH) pathway and up-regulation of metallothioneins I and genes of the family ERM (ezrin, radixin, and moesin). The main conclusions of our study are the confirmation of a global dysfunction of the synapses in the aged PFC and the evidence of opposite phenotypes of astrogliosis in the aging brain, which we report for the first time in the present article. © 2018 by the authors. Licensee MDPI, Basel, Switzerland.